Design, synthesis and antimalarial activity of novel bisN-[(pyrrolo[1, 2-a]quinoxalin-4-yl)benzyl]-3-aminopropylamine derivatives. (1st January 2017) - Guillon, Jean; Cohen, Anita; Gueddouda, Nassima Meriem; Das, Rabindra Nath; Moreau, Stéphane; Ronga, Luisa; Savrimoutou, Solène; Basmaciyan, Louise; Monnier, Alix; Monget, Myriam; Rubio, Sandra; Garnerin, Timothée; et al.
Abstract: Novel series of bis- and tris-pyrrolo[1, 2- a ]quinoxaline derivatives1 were synthesized and tested for in vitro activity upon the intraerythrocytic stage of W2 and 3D7 Plasmodium falciparum strains. Biological results showed good antimalarial activity with IC50 in the μM range. In attempting to investigate the large broad-spectrum antiprotozoal activities of these new derivatives, their properties toward Leishmania donovani were also investigated and revealed their selective antiplasmodial profile. In parallel, the in vitro cytotoxicity of these molecules was assessed on the human HepG2 cell line. Structure–activity relationships of these new synthetic compounds are discussed here. The bis-pyrrolo[1, 2- a ]quinoxalines1n and1p were identified as the most potent antimalarial candidates with selectivity index (SI) of 40.6 on W2 strain, and 39.25 on 3D7 strain, respectively. As the telomeres of the parasite could constitute an attractive target, we investigated the possibility of targeting Plasmodium telomeres by stabilizing the Plasmodium telomeric G-quadruplexes through a FRET melting assay by our new compounds.